Radio Compatibility Study of 1800MHz 5G System with Adjacent Frequency Systems - Liu, Lei; Wang, Jie (IEEE International Symposium on Broadband Multimedia Systems and Broadcasting, 2024)
This report analyzes the radio compatibility between 5 G systems in the 1800 MHz band and broadband TDD private networks in China, focusing on signal interference and its impact on network performance. It presents solutions like optimizing frequency allocation, implementing advanced interference management, and enhancing network capacity to improve communication quality and minimize interference. The report underscores the importance of continuous data analysis in driving technological innovation and network improvement. It highlights how understanding and addressing signal interference is crucial for enhancing user experience and supporting the future development of communications. The report emphasizes the significance of data-driven decision-making in the communications industry, suggesting that ongoing data analysis and adaptation to changing technologies and market demands will lead to more reliable and efficient communication services and technological advancements.